2013
DOI: 10.1179/1754762812y.0000000025
|View full text |Cite
|
Sign up to set email alerts
|

Audiologists’ knowledge of cochlear implants and their related referrals to the cochlear implant centre: Pilot study findings from UK

Abstract: The results show a trend that clinical scientists (audiology)/audiologists support cochlear implantation, but due to a lack of training and familiarity, not all are confident in discussing CIs with patients and making an appropriate referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…In die Hörgeräte-und CI-Versorgung sind derzeit unterschiedliche Berufsgruppen involviert. Daher ist davon auszugehen,dassdieMehrzahlderindieHörgeräteversorgunginvolvierten Berufsgruppen nicht über aktuelles CI-Expertenwissen verfügt und so durchaus den notwendigen Wechsel vom Hörgerät zum CI verzögert [16]. Hörgeräteträger mit unzureichendem Sprachverstehen gehören zum vertrauten Patientengut einer HNO-Praxis.HäufigmussdannohneumfangreichetechnischeMöglichkeiten zur Hörgeräteüberprüfung entschieden werden, ob der jeweilige Patient die Nutzung evtl.…”
Section: Diskussionunclassified
“…In die Hörgeräte-und CI-Versorgung sind derzeit unterschiedliche Berufsgruppen involviert. Daher ist davon auszugehen,dassdieMehrzahlderindieHörgeräteversorgunginvolvierten Berufsgruppen nicht über aktuelles CI-Expertenwissen verfügt und so durchaus den notwendigen Wechsel vom Hörgerät zum CI verzögert [16]. Hörgeräteträger mit unzureichendem Sprachverstehen gehören zum vertrauten Patientengut einer HNO-Praxis.HäufigmussdannohneumfangreichetechnischeMöglichkeiten zur Hörgeräteüberprüfung entschieden werden, ob der jeweilige Patient die Nutzung evtl.…”
Section: Diskussionunclassified
“…Despite the importance of information translation to increase the awareness of new knowledge and achieve change in audiences' actions or behaviours, pretrial qualitative research rarely seeks stakeholders' perspectives on dissemination strategies for RCT results. Adequate information in dissemination is of particular importance in audiology where hearing device knowledge amongst HCPs and patients is insufficient or compromised [13,17,18,37,38] and the uptake of both HAs and CIs is low [8][9][10]. Cohen et al [17], for example, found poor awareness of, and little knowledge about, CI eligibility criteria amongst primary care providers in the United States and recommended increased training and outreach by CI specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical equipoise is reinforced by personal preference and personal decision-making. HCPs may, for example, lack awareness of the benefits of CIs for patients with significant hearing loss which affects their assessment and referral for implantation, and limits informative discussions with patients [11,[17][18][19]. Decision-making processes can also be influenced by the commercial interests of hearing clinics where sales commissions and targets motivate some audiologists in their prescribing habits [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…It would be reasonable to assume that professionals such as audiologists and otorhinolaryngologists were well informed about the benefits and limitations of a CI and were able to refer appropriately. However, very little published data exists and the most recent of these studies, Chundu and Buhagiar, indicate that less than half of the audiologists surveyed were confident that they knew when to refer a patient for a CI assessment [46]. Behaviour patterns are explained and modified by using different theories of learning use models.…”
Section: Raising Awarenessmentioning
confidence: 99%
“…This cost refers to, but is not restricted to, financial outlays. Applying this into the area of disabling hearing loss, we must consider that people will take action to seek treatment for disabling hearing loss if they view this disabling hearing loss as a serious issue, they feel sufficiently concerned about the severity of their disabling hearing loss, and that there are more benefits than barriers to amplification or an alternative way of stimulation/amplification [46].…”
Section: Raising Awarenessmentioning
confidence: 99%